Dental health status in children with type 1 diabetes mellitus in Montenegro - Đuričković, Mirjana N; Ivanović, Mirjana (Vojnosanitetski pregled, 2021)
Background/Aim. The number of children with diabetes is constantly increasing. The aim of this study was to evaluate oral health in children with type 1 diabetes mellitus (T1DM) compared to healthy children. Methods. The study included 177 patients aged 10–15 years, divided into two groups. The group T1DM included children with type I diabetes mellitus, and healthy children were in the control group. Dental health was assessed using the decayed, missing, filled teeth (DMFT) index. The Plaque Index (PI), according to Silness-Löe, and the Calculus Index (CI) by Green, were used to determine oral hygiene. Salivary status involved determining the amount of secreted stimulated saliva and buffer capacity of the same patient. Results. In terms of average values of the DMFT index of permanent teeth, there were no statistically significant differences between the groups. A significant difference (p = 0.001) was found in the PI value between the T1DM group (1.29 ± 0.56) and the control group (1.01 ± 0.50). Also, a significant difference was found in the CI value between the T1DM group (0.09 ± 0.23) and the control group (0.03 ± 0.14) (p = 0.047). The average amount of secreted stimulated saliva for diabetic children was significantly lower (0.99 ± 0.14 mL/min) compared to healthy children (1.06 ± 0.20 mL/min) (p = 0.020). Conclusion. Children with T1DM do not have more diseased teeth; however, they have more dental plaque, dental calculus, and lower salivation than the children in the control group. Also, our results point to the absence of preventive measures and programs in maintaining dental health in Montenegro.
Keywords: child; dental caries; dmf index; diabetes mellitus, type 1; oral health; oral hygiene; saliva